2004
DOI: 10.1537/ase.00086
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes of JC virus in Southeast Asia and the western Pacific: implications for human migrations from Asia to the Pacific

Abstract: JC virus (JCV) genotyping is a novel method of tracing human migrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…According to the phylogenetic tree (Figure 2), the SC isolates worldwide can be classified into several clusters, previously designated SC-a to -f and SC-x (Saruwatari et al, 2002b;Takasaka et al, 2004), with BPs ranging from 46% to 100%. Although the BP for SC-f was not high (63%), we found that all SC-f isolates examined carried a unique pentanucleotide deletion in the transcriptional control region (Saruwatari et al, 2002b), whereas this deletion was absent in all other subgroups (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…According to the phylogenetic tree (Figure 2), the SC isolates worldwide can be classified into several clusters, previously designated SC-a to -f and SC-x (Saruwatari et al, 2002b;Takasaka et al, 2004), with BPs ranging from 46% to 100%. Although the BP for SC-f was not high (63%), we found that all SC-f isolates examined carried a unique pentanucleotide deletion in the transcriptional control region (Saruwatari et al, 2002b), whereas this deletion was absent in all other subgroups (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Based on this SNP, we subclassified a large number of SC isolates worldwide into SC-f or non-SC-f subgroups (Table 3). The findings shown in Table 3 can be summarized as follows: (1) SC-f isolates predominated in all regions of China, with only the occasional occurrence of non-SC-f; (2) non-SC-f isolates predominated in one region of Thailand and most regions of Myanmar, with the exception of Peinnebeen, where isolates classified as SC-f were mainly detected; (3) SC-f isolates predominated in two regions of Vietnam and in single regions in Malaysia and Indonesia; (4) SC-f isolates predominated in three islands in the Philippines, although non-SC-f isolates occurred at lower but significant rates (P < 0.01 vs. Hanoi and Danang; Fisher's exact test) in two islands (Luzon and Cebu) of the Philippines, these were previously identified as a unique subgroup (SC-x) of the SC genotype (Miranda et al, 2003;Takasaka et al, 2004); (5) only SC-f isolates occurred in regions (e.g. southern Africa and southern Japan) remote from the areas where SC is most common (i.e.…”
Section: Classification Of Sc Isolates Worldwide Into Sc-f and Non-scmentioning
confidence: 99%
See 3 more Smart Citations